The operationalization of the study: global carriers and neoliberal thinking - Pohlmann, Markus; Elias, Friederike (Global economic elites and the new spirit of capitalism, 2024)
In each country study qualitative, quantitative research steps are combined in order to empirically test the basic assumptions that form the core of the convergence paradigm (# see Pohlmann, Chap. 2, p). Aquantitative life course analysis will be conducted to find out whether economic globalization leads to the establishment of a “transnational management” that is recruited internationally, whether these managers have similar education pattern.
Gesehen am 27.06.2024